Pauline Elizabeth Hopkins Black daughter of the Revolution - Brown, Lois, 1966- (Chapel Hill : University of North Carolina Press, 2008)
"In this critical biography, Lois Brown documents for the first time Pauline Elizabeth Hopkins's early family life and her ancestral connections to eighteenth-century New England, the African slave trade, and twentieth-century race activism in the North." "Richly grounded in archival sources, Brown's work offers a definitive study that clarifies a number of inconsistencies in earlier writing about Hopkins. Brown re-creates the life of a remarkable woman in the context of her times, revealing Hopkins as the descendant of a family comprising many distinguished individuals, an active participant and supporter of the arts, a woman of stature among professional peers and clubwomen, a literary editor and author, and a gracious and outspoken crusader for African American rights."--Jacket.
Black daughter, Black history -- Patriarchal facts and fictions -- The creation of a Boston family -- Progressive arts and the public sphere -- Dramatic freedom : The slaves' escape; or, The underground railroad -- Spectacular matters : "Boston's favorite colored soprano" and entertainment culture in New England -- Literary advocacy : women's work, race activism, and lynching -- For humanity : the public work of Contending forces -- Contending forces as ancestral narrative -- Cooperative enterprises -- (Wo)manly testimony : the Colored American magazine and public history -- Love, loss, and the reconstitution of paradise : Hagar's daughter and the work of mystery -- "Boyish hopes" and the politics of brotherhood : Winona, a tale of Negro life in the South and Southwest -- The souls and spirits of Black folk : pan-Africanism and racial recovery in Of one blood and other writings -- Witness to the truth : the public and private demise of the Colored American magazine -- The Colored American magazine in New York City -- New alliances : Pauline Hopkins and the Voice of the Negro -- Well known as a race writer : Pauline Hopkins as public intellectual -- The New era magazine and a "singlewoman of Boston" -- Cambridge days.
Includes bibliographical references (p. [631]-664) and index.
Description based on print version record.
Keywords: Hopkins, Pauline E; Authors, American -- 19th century -- Biography; Authors, American -- 20th century -- Biography; African American women authors -- Biography; African American journalists -- Biography; African American women -- Intellectual life; African Americans in literature; African Americans -- History -- 1877-1964.; Racism -- United States -- History -- 20th century; United States -- Race relations -- History -- 20th century; Hopkins, Pauline E; Hopkins, Pauline Elizabeth -- Biographie; BIOGRAPHY & AUTOBIOGRAPHY / Literary; LITERARY CRITICISM / American / General; Biographie; Electronic books